Personal Growth in Women After Husband's Death - Innes Yonanda; Sartini Nuryoto; Siti Urbayatun (Psikostudia : Jurnal Psikologi, 2022)
The death of a spouse is one of the saddest major life events. These events can cause trauma and make the individual's life negative. This phenomenon is in sync with the aim of this study is to reveal the process of post-traumatic growth and describe the aspects that affect post-traumatic growth. This study uses a qualitative analysis of the type of phenomenology. Furthermore, the analysis used is a theme analysis of the major themes expressed by the respondents. The sample is 6 widows who have been collected using purposive sampling. The semi-structured interview involved 4 questions. The findings of this study are the process of discovering post-traumatic growth such as how to do self-disclosure, carry out deep reflection and manage emotions until growth is achieved. PTG in the context of this research, such as the establishment of relationships with other people, the existence of new possibilities, self-strength is increasingly visible, spiritual changes are getting better and the appreciation of life is getting stronger. Individuals who have achieved growth will also develop more abilities than before, namely increasing relationships with others, new possibilities and patterns, recognizing inner strengths, increasing spirituality, and having new life priorities. Kematian pasangan merupakan salah satu major life events paling menyedihkan. PeristIwa tersebut dapat mengakibatkan trauma dan membuat hidup individu menjadi negatif. Fenomena ini sinkron dengan tujuan penelitian ini adalah untuk mengungkapkan proses post traumatic growth dan mendeskripsikan aspek-aspek yang mempengaruhi post traumatic growth. Penelitian ini menggunakan analisis kualitatif jenis fenomenologi. Lebih lanjut, analisis yang digunakan adalah analisis tema dari tema-tema besar yang diungkapkan responden. Sampelnya adalah 6 orang berstatus janda yang telah dikumpulkan menggunakan purposive sampling. Semi terstruktur untuk wawancaranya melibatkan 4 pertanyaan. Temuan penelitian ini adalah proses penemuan pertumbuhan pasca trauma seperti cara melakukan pengungkapan diri, melakukan perenungan yang mendalam dan melakukan pengelolaan emosi hingga tercapainya growth. PTG dalam konteks penelitian ini seperti terjalinnya hubungan dengan orang lain, adanya kemungkinan baru, kekuatan diri semakin nampak, perubahan spiritual semakin lebih baik dan penghargaan hidup semakin menguat. Individu yang telah mencapai growth juga akan mengembangkan kemampuan yang lebih dari sebelumnya yaitu meningkatnya hubungan dengan orang lain, adanya kemungkinan dan pola baru, mengenal kekuatan dalam diri, peningkatan dalam hal spiritualitas, serta memiliki prioritas hidup baru.